The location and the nature of Airbnb listings in Johannesburg and their impact on property prices and the availability of long term rental stock - Niselow, Tehillah (My University, 2019)
The popularity of the digital or the ‘shared economy’ has become almost ubiquitous amongst the middle and upper classes in developing and developed countries. Many people wonder how they managed before ride hailing applications such as Uber and short-term accommodation rental applications such as Airbnb. These technologies have changed the face of commuting and travelling within cities as well as travel for business people and holiday makers. Despite the relative novelty of these technologies, there have been concerns raised about their impact on labour rights and housing prices in some countries. Regulators in several of the world’s tourism hotspots such as London, New York and Amsterdam have stepped in to create controls around Airbnb to mitigate concerns about rising property prices affecting locals. In South Africa, there has been anecdotal reportage in the media about the link between the popularity of Airbnb and rising property prices in Cape Town. While Cape Town has received more attention, the number of Airbnb listings in Johannesburg is growing, though still relatively small compared to other metropolitan cities in the world. No large-scale study has been undertaken into the phenomenon in both cities by government authorities or academic scholars. This research report looks at the nature and location of Airbnb listings in Johannesburg as well as data on rental and property prices in Johannesburg and nationwide over the last five years. In the report, I also make use of interviews with real-estate agents and city planning authorities to consider whether Airbnb has impacted housing prices or spatial patterns. This report concludes that most Airbnb listings are located within areas in Johannesburg that are already well connected to economic opportunities and infrastructure. In addition, the research shows that Johannesburg, a city in a state of flux and ever evolving, is not like cities within developed countries with relatively stable economies. Due to difficult economic conditions in recent years and weaker property prices as well as rental incomes, it is not possible to find a correlation between the rise of Airbnb and property prices.
Research report submitted in partial fulfilment of requirements of Master of Arts in Development Studies, in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, March 2019
Keywords: Real property--South Africa; Real estate agents--South Africa; Residential real estate--South Africa